IMPROVING EMPLOYEE PERFORMANCE: WORK RESPONSIBILITIES THE PUBLIC WORKS AND SPATIAL PLANNING OFFICE OF LEBAK REGENCY - Ryan Firdiansyah Suryawan; Nik Nik Ahmad Munawar; Yumhi Yumhi; Mohamad Ikbal (Sosiohumaniora, 2023)
This study aims to determine the effect of task complexity and self-efficacy on employee performance at the PUPR Office of Lebak Regency. The analysis examines the effect of locus of control, task complexity and self-efficacy on employee performance. The method used is a quantitative survey using techniques path analysis data processing. The population in this study were employees of the Public Works and Public Housing Service who were registered in the employment data as many as 87 people. Sampling uses a simple random technique, where the sample is selected at random, regardless of the population level, all elements in the population have an equal chance, so that they can be selected as subjects. The results of the study found that the PUPR Office of Lebak Regency needs to consider employee responsibilities, employee trust, and provide complex assignments as part of efforts to improve employee performance. This can be seen from the direct positive and significant influence of locus of control and task efficacy on self-efficacy and employee performance. Another finding is that there is an indirect effect of task complexity and locus control on employee performance through self-efficacy. There is a positive and significant indirect effect of locus of control and task efficacy on employee performance, this indicates that an increase in the locus of control and task complexity will result in an increase in employee performance.